The physics of the Manhattan project - Reed, Bruce Cameron (Springer Berlin Heidelberg, 2011)
The development of nuclear weapons during the Manhattan Project is one of the most significant scientific events of the twentieth century. This book, prepared by a gifted teacher of physics, explores the challenges that faced the members of the Manhattan project. In doing so it gives a clear introduction to fission weapons at the level of an upper-level undergraduate physics student. Details of nuclear reactions, their energy release, the fission process, how critical masses can be estimated, how fissile materials are produced, and what factors complicate bomb design are covered. An extensive list of references and a number of problems for self-study are included. Links are given to several spreadsheets with which users can run many of the calculations for themselves.